Philosophy and political agency in the writings of Frederick II of Prussia - Lifschitz, A (Cambridge University Press, 2020)
Frederick II’s writings have conventionally been viewed either as political tools or as means of public self-fashioning – part of his campaign to raise the status of Prussia from middling principality to great power. This article, by contrast, argues that Frederick’s works must also be taken seriously on their own terms, and interpreted against the background of Enlightenment philosophy. Frederick’s notions of kingship and state service were not governed mostly by a principle of pure morality or 'humanitarianism', as argued influentially by Friedrich Meinecke. On the contrary, the king's views were part and parcel of an eighteenth-century vision of modern kingship in commercial society, based on the benign pursuit of self-love and luxury. A close analysis of Frederick's writings demonstrates that authorial labour was integral to his political agency, publicly placing constraints on what could be perceived as legitimate conduct, rather than mere intellectual window-dressing or an Enlightened pastime in irresolvable tension with his politics.